Computed tomography perfusion imaging-guided intravenous thrombolysis in acute minor ischemic stroke - Sartor-Pfeiffer, Jennifer; Lingel, Mirjam; Stefanou, Maria-Ioanna; Krumbholz, Markus; Hennersdorf, Florian; Ernemann, Ulrike; Poli, Sven; Feil, Katharina; Ziemann, Ulf; Mengel, Annerose (Frontiers in Neurology, 2023)
Background Over 50% of acute ischemic stroke (AIS) patients present with minor neurological deficits, and optimal treatment is still debated. The randomized PRISMS trial did not show beneficial effects of intravenous thrombolysis (IVT) in unselected patients with minor stroke and non-disabling neurological deficits. Purpose The study aimed to evaluate if AIS patients with minor stroke may benefit from computed-tomography-perfusion (CTP)-guided IVT. The primary endpoint was good functional outcomes, defined as a modified Rankin Scale score of 0–2 at 90 days. Methods AIS patients with a NIHSS of ≤5 presenting within 4.5 h underwent multimodal CT-imaging including CTP. CTP mismatch was defined as hypoperfusion on CTP with time-to-peak delay >6 s without corresponding hypoperfusion in cerebral blood volume. IVT decision was left to the attending stroke physicians. Patients with large vessel occlusion (LVO) and absolute contraindications to IVT were excluded. Results In total, 267 consecutive patients were included [mean age: 72 ± 14 years, 45.3% female patients, 75.3% received IVT, median NIHSS on admission: 3 (IQR 2, 4)]. CTP mismatch was detected in 41.8% of IVT− treated patients (IVT+) and 28.8% of standard treatment patients (IVT−) (p = 0.06). IVT+ had favorable outcomes at 90 days compared to IVT− (p = 0.006), but no interaction with an existing CTP mismatch was detected (ORadj: 1.676; 95% CI: 0.644–4.364). No symptomatic intracranial hemorrhage according to ECASS-III criteria occurred. Conclusion Although selected AIS patients with minor stroke may benefit from IVT, CTP mismatch does not correlate with functional outcomes. No benefit from CTP mismatch in guiding IVT was detected in patients without LVO presenting with minor neurological deficits.